(untitled) (Environment & Health, 2023)
Introduction. Accidents are one of the causes of work-related mortality and disability. According to the ILO estimates, about 2.3 million men and women in the world die each year as a result of workplace accidents or work-related diseases. In recent years, a gradual decrease in the level of industrial injuries (II) has been noted in Ukraine. Statistical indicators indicate the complexity of the situation regarding the formation of the number of injuries at work, depending on socio-economic conditions, the state of labor protection, medical and demographic characteristics of workers, changes in legislation regarding compliance with international requirements. II is closely related to the level of GDP, financial crises, as well as such challenges of the time as the COVID-19 pandemic, the conduct of military operations after the invasion of the Russian Federation in Ukraine, the occurrence of danger when performing work in the conditions of hostilities. The purpose of the study is to reveal the regularities of the formation of indicators of industrial injuries in Ukraine during the years of independence, in the conditions of the COVID-19 pandemic, during the period of martial law. Research materials and methods of studying the prevalence of industrial injuries was carried out according to the principle of continuous statistical sampling of primary documents compiled for all cases of occupational accidents first detected and registered in Ukraine, for the years 1991-2022. The analysis of II was carried out by types of economic activity. The materials were processed in accordance with the tasks set by classical methods of medical statistics, the relationship between statistical indicators was determined using the Spearman correlation coefficient to assess the relationship of individual indicators. Research results and their discussion. During the years of independence, the formation of II indicators was determined by the factors of socio-economic, regulatory and legal transformations, the number and employment of the population in the labor process. The coefficient of frequency of accidents (CFA) is on average 0.31, while in the coal industry - 7.89, transport - 1.6, agriculture - 1.14, mining and non-metal industry - 0.99%, metallurgical industry – 0.96, mechanical engineering - 0.48. The weight coefficient - CW has a somewhat different ranking, with an average Kт of 26.42, the first place belongs to transport - 65.02, the second - to the mining and non-mineral industry - 48.13, the third - to the coal industry - 36.96, the fourth - to the metallurgical industry - 32 ,8, the fifth - construction - 32.72, the sixth - gas industry - 31.08, the next - machine building - 26.32. The number of cases of COVID-19 among medical workers has significantly decreased from 2020 to 2022. A significant number of accidents were registered among those working during the performance of labor duties in the conditions of hostilities at critical life support enterprises, such as oil and gas production, state administration and defense, electricity supply, transport, engineering, health care. Conclusions: 1. Over the years of independence, there has been a significant decrease in the total number of workplace injuries. In 2022, the total number of injuries decreased by more than 40.0 times compared to 1992, the number of deaths at work - by more than 5.0 times. 2. The level of injury depends on the challenges of time in certain defined periods of the formation of the state, which causes fluctuations or a surge in occupational accidents. 3. The assessment of the relationship between GDP and structural changes in II (the Is index) reflects the percentage of fatal cases in the structure of injuries, and is one of the indicative characteristics of the state of labor protection in Ukraine. The increase in GDP in the period 1992-2014 correlates with Is rs=0.97 (Spearman correlation coefficient p